Guidelines for enabling conditions and conditional modifiers in layers of protection analysis (LOPA) (Wiley, 2013)
The initial Layer of protection analysis (LOPA) book published in 2001 set the rules and approaches for using LOPA as an intermediate method between purely qualitative hazards evaluation/analysis and more quantitative analysis methods. Basic LOPA provides an order-of-magnitude risk estimate of risk with fairly reproducible results. LOPA results are considered critical in determining safety integrity level for design of safety instrumented systems. This guideline clarifies key concepts and reinforces the limitations and the requirements of LOPA. The main scope of the gu.
Keywords: Chemical processes -- Safety measures.; Chemical processes -- Safety standards.; elektronické knihy; electronic books